Thermal improvement in magnetized nanofluid for multiple shapes nanoparticles over radiative rotating disk - Adnan (Elsevier, 2022)
In the present time, thermal transportation in the colloidal suspensions under various scenario becomes an influential research direction due to their extensive applications. Therefore, investigation of thermal transport over a rotating disk under the impacts of thermal and velocity slip, imposed Lorentz forces and thermal radiation is conducted for multiple shape effects of the nanomaterial. The nanofluid model suspended by Al2O3, TiO2 and Cu nanomaterial is reduced in dimensionless version via similarity variables. After that, RK scheme is implemented and handle the model effectively. The outcomes of various parameters for the velocity, thermal transport, skin friction and local heat transport are sketched and explained broadly. It is examined that the heat transport for the nanofluids becomes dominant throughout the analysis in comparison with conventional liquid. The temperature of the nanofluids significantly enhances due to the velocity slip effects. Moreover, thermal radiation and the volumetric fraction of the nanomaterials favor the local heat transfer rate.